Contrastive Linguistics, Translation, and Parallel Corpora - Ebeling, Jarle (Meta, 1998)
AbstractThis paper regards parallel corpora as suitable sources of data for investigating the differences and similarities between languages, and adopts the notion of translation equivalence as a methodology for contrastive analysis. It uses a bidirectional parallel corpus of Norwegian and English texts to examine the behaviour of presentative English there-constructions as well as the Norwegian equivalent det-constructions in original and translated English, and original and translated Norwegian respectively.